Valuation and accounting of operating and capital lease in the lessee financial books and their influence on the financial situation of the company - Trzeciak, Ewelina (Journal of Finance and Financial Law, 2019)
The article presents the accounting of lease agreements on the example of simulations. It shows the valuations of lease contracts that the author has made in a spreadsheet. Records show only the first year of lease. It includes data from the valuation of lease agreements with a description the value of which is the cost, income, asset or liability. A financial analysis was also carried out using financial indicators, which shows the impact of lease on the financial situation of the company.